Karakteristik klinikopatologi karsinoma kolorektal di RSUP Sanglah, Bali, Indonesia tahun 2013-2017 - Venosha Gunasekaran; Ni Putu Ekawati; I Wayan Juli Sumadi (DiscoverSys Inc., 2019)
Background: Colorectal cancer is the third most common cancer in the world and the fourth leading cause of cancer death. The etiology of colorectal carcinoma is an unhealthy lifestyle and a poor diet such as excessive consumption of fat. This study aims to determine the characteristic of the clinicoopatological on colorectal carcinoma patients at Sanglah Hospital Denpasar 2013-2017.Methods: A cross-sectional study was conducted with a purposive sampling technique, on all patients who met the inclusion criteria. The tools used in data collection are medical records and their complaints that are found in the Anatomy Department of Sanglah Hospital. Data recorded includes age, grade, stage, and histopathology. The data analysis method uses SPSS version 17 for Windows.Results: A total of 121 cases were collected where most were in the age range of 50-60 years, as many as 48 cases (39.7%). In addition, Grade 2 was 98 cases (81.0%), followed by histopathological type with adenocarcinoma not otherwise specified as many as 118 cases (97.5%). Stadium 2 cases were 65 cases (53.7%), and 72 cases (59.5%) were males.Conclusion: Most cases are in the range of 50-60 years of age which is followed by Grade 2, histopathological type of adenocarcinoma not otherwise specified, stage 2 and male sex